Nunnery Life in 16th Century Wallachia – Muşa/Magdalina before and after Taking Vows - Ilie, Liviu Marius (Studia Ceranea, 2023)
The Wallachian monasteries are very well documented in the 16th century, but the life of nuns or monks after joining the monastery is a lesser-known aspect. Various details can be found in the life of a noblewoman (taking the name of Mușa), who decided to become a nun (Magdalina) during the first years of the 16th century. Mușa’s life before entering the monastery is not very well known. Although many researchers tried to link her to the Craiovescu family, one of the most influential families in Wallachia at that time, this paper argues against this opinion. The historical sources describe her as a relative of a Wallachian nobleman, Cârjeu, and as the wife of Hamza, another important nobleman from the first decades of the 16th century. Mușa took vows in the monastery, which she built, and even after she became a nun, she preserved some of her former habits. Thus, the nun Magdalina kept in her possession villages and Roma families, which she donated to different monasteries, a widespread situation in the Byzantine monasticism. Although the sources did not describe her everyday life as a nun, they documented her relations with the political and ecclesiastical elites.